The Importance of Physical Exercise in the Lives of Women Who Are Involved in Physical Education and Sports (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Women of different ages engage in physical exercise mainly for two purposes, one of which is to improve their health, and the other is to stand side by side with men in sports, demonstrate their capabilities, and defend their honor. As is known, the number of women involved in physical education and sports is increasing year by year. This is due to the daily development of sports in our republic and the changes taking place in our lifestyle. The working capacity of the female body is slightly lower than the working capacity of the male body, which is due to the anatomical and physiological characteristics of the female body.